Characterization and phase transformation study of TlSbSe2 crystals - Chrissafis, K.; Özer, Mehmet; Vinga, E.; Polychroniadis, E.; Chatzistavrou, X.; Paraskevopoulos, K. M. (SPRINGER, VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS, 2006)
TlSbSe2 monocrystals were grown using the modified Bridgman-Stockbarger method and were characterized by transmission electron microscopy (TEM) and X-ray diffraction (XRD). Reflectivity spectra have been registered in the range 50 to 4000 cm(-1) for E parallel to a and E parallel to b polarizations, on the cleavage plane. A remarkable anisotropy at two directions was verified. With regard to previous observations, additional peaks were discriminated and the fundamental phonon parameters were determined using classical dispersion relations. The material presents a complex phase transformation - with two thermal effects - that was examined using differential scanning calorimetry (DSC). Non-isothermal measurements, at different heating and cooling rates (beta), were used to study the thermal phenomena. The main effect is attributed to a structural displacement and the second one to a cation exchange procedure. The phase transformation temperature depends strongly on the cooling rate and the peaks are shifted by 30 K with the increase of this rate, on the contrary to the increase of the heating rate that has a smaller effect. Phenomena related with the influence of the previous, repeated heating and cooling cycles on the transformation are also examined and analytically discussed.
Keywords: non-isothermal calculations DSC; phase transformation; polarized reflectivity spectra; TlSbSe2; compound TLSBSE2; microscopy; izotermal olmayan hesaplamalar DSC; faz dönüşümü; polarize yansıma spektrumları; bileşik TLSBSE2; mikroskopla inceleme